Aspectos do romance em Mato Grosso : um estudo sobre Mirko, de Francisco Bianco Filho - Rodrigues, Cibele Antônia de Souza (2011)
The nineteenth century Brazil, guided by theories of European thought, was marked by the country's modernization project, unleashed by the establishment of the royal family at Rio de Janeiro in 1808. This idea presupposes a certain degree of economic development, however, as this took place unevenly, their results were also different. While Rio de Janeiro in the early twentieth century, had already formed a literary field, Mato Grosso had not yet. The circulation of ideas and literature happened basically through the journals, which contributed to the formation of readers. The literature of Mato Grosso was influenced by Dom Aquino, major name in local literature and defender of the classical tradition. There was circulation of novels, as researches prove, by foreign and national writers, but none locally produced. The novel in its emergence in Europe, as in its establishment in Brazil, was related to social changes that promoted changes in the conceptions of world and literature. In the context of Mato Grosso the construction of the literary field presented its own characteristics, as it responded to specific stimuli and conditions, generating a peculiar temporality. Based on these observations, our choice of study was the novel Mirko (1927), by Francisco Bianco Filho, because, even though it does not refer to Mato Grosso, it corresponds to the idea of current literature and has been written by a prominent figure in the society of that time, politically and intellectually. These factors led the work to be contemplated by the literary historiographies of Mato Grosso, as well for instances of consecration such as the Mato Grosso State Academy of Letters. Your choice to discuss certain aspects of culture and literature in the State in the late nineteenth century and its development in the early twentieth century was due primarily to certain aesthetic traits, such as the confluence of literary styles and a kind of widespread regionalism.